Growth-promoting hormonal alterations in pregnant women living with HIV receiving dolutegravir-based antiretroviral treatment are associated with lower infant 1-year weight z-scores - Powis, Kathleen M.; Jao, Jennifer; Legbedze, Justine; Dunk, Caroline; Mmasa, Keolebogile N.; Kgole, Samuel W.; Masasa, Gosego; Mohammed, Terence; Makhema, Joseph; Moyo, Sikhulile; Geffner, Mitchell E.; Abrams, Elaine J.; et al. (Frontiers in Pediatrics, 2025)
BackgroundSeveral maternal hormones regulate fetal growth, but concentrations of these hormones in pregnancy among women living with HIV and associations between hormone levels and infant anthropometrics is limited.MethodsPregnant women with HIV receiving dolutegravir/tenofovir/emtricitabine and HIV-seronegative women and their infants prospectively enrolled in the Botswana-based Tshilo Dikotla study were included in this analysis. Estradiol, sex-hormone binding globulin (SHBG), progesterone, cortisol, pituitary growth hormone-1 (GH1), insulin-like growth factor-1 (IGF-1), and insulin-like growth factor binding protein-1 (IGFBP-1) concentrations were measured in maternal plasma collected between 24 and 29 weeks’ gestation. Bioavailable estradiol was derived using estradiol and SHBG concentrations. Generalized linear models were fit to evaluate associations between HIV status and each maternal hormone. Similar models were fit to assess effect modification by HIV status on the relationship between each maternal hormone and infant anthropometrics at birth and 1-year of age.ResultsMaternal plasma specimens were available from 114 women (46 with HIV). Women with HIV had lower mean log bioavailable estradiol (β: −0.22, p = 0.031), cortisol (β: −0.22, p = 0.001), and IGF-1 (β: −0.81, p = 0.007), but higher GH1 (β: 0.91, p = 0.007) than women without HIV. Infant HIV-exposure status modified associations of log GH1 (β: −0.21, p = 0.05) and log IGF-1 (β: 0.40, p = 0.004) with infant 1-year weight-for-age z-score (WAZ), adjusting for maternal age, BMI, exclusive breastfeeding duration, and birth WAZ. Among infants who were HIV exposed uninfected, lower GH1 and higher IGF1 levels were associated with higher WAZ at 1 year of age. These associations were not observed in HIV-unexposed infants.ConclusionAssociations between maternal growth-promoting hormones and infant weight at 1 year of life differ significantly by maternal HIV status, reflecting potential perturbations in the maternal-fetal-infant growth axis among pregnant women with HIV. Additional research is needed to identify mechanisms and possible interventions.